Comparison of product visualizations on consumer learning in e-commerce - Lau, Chiew Hoon (Universiti Malaysia Sarawak, (UNIMAS), 2015)
E-commerce has become increasingly popular in this era of globalization due to its convenience to both vendors and buyers conducting their business and purchase through the internet. The first thing consumers need to do when engaging with an e-commerce website is to learn about the particular product before deciding whether to purchase or not. Product visualization can improve consumer learning hence playing a significant role in influencing the consumer's buying behaviour. This project aims to compare the effect of product visualization using static 2-D and interactive 3-D product visualization on consumer learning. In addition, this study also investigate the influences ofthe interactivity on consumer learning. Two webpages with static 2-D and interactive 3-D product visualization respectively were developed and evaluated through experimental research using betweensubject design methodology. Sixty participants were selected randomly using convenient sampling method where the data is analysed using the Independent Samples T -Test with SPSS. From the result, it is shown that interactive 3-D product visualization in an ecommerce website positively influences the product knowledge, brand attitude, and purchase intention ofconsumers. We also found that interactivity in interactive 3-D product visualization enhances the consumer learning as compared to the static 2-D product visualization. These results highlighted the importance of product visualization and interactivity on consumers' buying behaviour.